1. The problem statement, all variables and given/known data The lagrange equations are obtained as in the picture. I am only showing the final part of the solution, where they consider the final case of x≠y≠z. 2. Relevant equations The equation at the second paragraph is obtained by subtracting: (5.34 - 5.35). The final equations are obtained by dividing 5.37 by (x-y) throughout, same for the other 2. (Which is ok, since x - y ≠ 0) 3. The attempt at a solution I understand their method, but why can't I just do this: (5.34) + (5.35) + (5.36) 3(x2 + y2 + z2) + 2λ(x + y + z) + 3μ = 0 Using the constraints, 3(1) + 0 + 3λ = 0 λ = -1 Not sure if this is a appropriate solution..